Rotación de personal en el peaje Andes - Rodríguez Alfonso, Diego Alexánder (Corporación Universitaria Minuto de Dios, 2023)
Esta práctica profesional se llevó a cabo en el peaje Andes, en la modalidad de contrato de aprendizaje bajo la dirección de la empresa Regency SAS cuya actividad operacional es recaudar y transportar el dinero de un gran número de peajes en el País, desde el peaje Andes se controlan dos peajes más, el peaje Fusca y el peaje Unisabana, mi Fuente: Coordinación de prácticas profesionales Administración de Empresas-Sede-Centro Regional ZipaquiráUNIMINUTO. El periodo de práctica se desempeñó desde el 27 de Mayo de 2022, hasta el 26 de Noviembre de 2022, durante esta etapa se desempeñaron labores de gran relevancia como estudiante de administración de empresas. El modelo operativo de los peajes hace que sea necesario la implementación de turnos rotativos de trabajo, de acuerdo con las necesidades de la operación y como contingencia para garantizar la operatividad durante las 24 horas se podrán hacer ajustes a los turnos establecidos, especialmente en los fines de semana y puentes festivos.

This professional practice was carried out in the Andes toll, in the form of an apprenticeship contract under the direction of the company Regency SAS whose operational activity is to collect and transport money from a large number of tolls in the country, from the Andes toll Two more tolls are controlled, the Fusca toll and the Unisabana toll, my Source: Coordination of Professional Practices Business Administration-Headquarters-Zipaquirá Regional Center-UNIMINUTO. The internship period was carried out from May 27, 2022, to November 26, 2022. During this stage, highly relevant tasks were carried out as a business administration student. The operating model of tolls makes it necessary to implement rotating work shifts, according to the needs of the operation and as a contingency to guarantee 24-hour operation, adjustments may be made to the established shifts, especially on weekends. weekends and bank holidays. V Due to the nature of the collection operation according to traffic, the personnel is available in the required function in the most appropriate way, optimizing the plant of operational personnel, without generating excesses and maintaining the levels of attention established for users and control required. To this end, standards, policies and procedures oriented towards the optimal development of said operation have been implemented. These Procedures are divided according to the function that is being developed, in the collection stations. As an intern I managed to realize the importance of the human factor, it is very important for this process, since it is people who have direct contact with road users. For this reason, for each employment relationship, a theoretical and practical pre-selection and induction procedure is carried out. In general terms, the greatest threat that the toll was presenting was due to the lack of commitment of the collaborators, there were unjustified absences and due to the lack of personnel, many times they were only called to their attention without receiving any sanction beyond deduct the salary for the day not worked, this lack of commitment was due to the way in which the hiring was being carried out and the profile of people who were entering to work, the company Regency SAS has its headquarters in Cali, Valle del Cauca, reason by which the hiring was carried out remotely, the interviews were virtual and most of the time the company, in an effort to meet the number of workers required by the toll coordinator, hired young people who were having their first experience work and for this reason it was not possible to create a bond with a sense of belonging, most of these people carried out their work for one or two weeks, waited for the first payment and resigned, the working conditions in this place require something more than the desire to earn money, the people with the greatest durability in this job are all those who have responsibilities, children, debts, the fact that there is a situation with which they VI must comply in a mandatory manner, based on this situation the company was making a contract based in meeting the number of workers regardless of the profile of the person, which triggers a constant turnover of staff.
Proponer estrategias de mejora que permitan disminuir el índice de rotación de personal, a partir de los resultados encontrados en el análisis de las entrevistas de retiro.
Keywords: Rotación de personal; Bienestar; talento humano; Estabilidad laboral; Rotation; welfare; human talent, happiness; growth; stability